Risk-adjusted proposal for >60 months follow up after surgical treatment of organ-confined renal cell carcinoma according to life expectancy - Frees, Sebastian; Thüroff, Joachim W. (International journal of urology, 2019)
Objectives: To determine the long-term oncological outcome of organ-confined (<pT3) renal cell carcinoma. Methods: We identified 889 patients with complete long-term follow-up data, who had been surgically treated for renal cell carcinoma (<T3) at our institution between 1976 and 2009. Kaplan-Meier analysis was used to assess the incidence and time interval of recurrence defined as local recurrences or metastases. We further compared patients who had tumor progression before or after 60 months. Results: After a median follow-up period of 74.33 months (range 3-329 months), 44 patients (4.9%) had disease recurrence. A total of 38.6% of the recurrences occurred after 60 months; 76.2% of patients had distant metastases and 23.8% of patients had local recurrences. In patients with low-grade (G1) and low-stage (pT1a) tumors, there was a trend to develop recurrence or metastases after longer intervals. Patients with lung metastasis and patients with multiple metastatic locations developed these metastases earlier than patients with bone metastasis. The risk of dying of other causes correlated with age, but the time interval to metastases did not. Conclusions: Current guidelines recommend a follow-up period of 60 months after surgical treatment of organ-confined renal cell carcinoma. Our data shows that one-third of recurrences of <pT3 renal cell carcinoma occur after 60 months. According to our oncological analysis, we suggest an age-adjusted strategy of follow-up balancing the risk of tumor recurrence and the life expectancy of the patient.